Bridging the Implementation of Nagoya-Kualalumpur Supplementary Protocol on Liability and Redress in Indonesia - Santoso, Wahyu Yun (UI Scholars Hub, 2016)
Aside the Nagoya Protocol on Access and Benefit Sharing, which is already ratified by Indonesian government with Law No. 11 Year 2013, the Nagoya–Kuala Lumpur Supplementary Protocol on Liability and Redress (NKL Supplementary Protocol) offers great benefits for “megabiodiversity” country like Indonesia. Despite the lack of awareness of this supplementary protocol, the need for ratifying is urge. This legal-normative research aims to seek the existing regulation in Indonesia to support the implementation of the Nagoya–Kuala Lumpur Supplementary Protocol on Liability and Redress, and to explore the readiness of the national legal system on liability and redress for biodiversity. Based on the several existing regulation, Indonesia, to some extent has the readiness to implement the Nagoya–Kuala Lumpur Supplementary Protocol on Liability and Redress. This finding should be supported with more intens discussion on the protocol.